2022
DOI: 10.3390/antiox11061068
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Chrysanthemum morifolium (Chuju) Extract on H2O2-Treated L-O2 Cells as Revealed by LC/MS-Based Metabolic Profiling

Abstract: Chrysanthemum has a long history of being used to attenuate various oxidative stress-related discomforts and diseases; however, its mechanisms remain unclear. In this study, the antioxidant effect of chrysanthemum aqueous extract was investigated, and the potential mechanisms were explored via a metabolomics study. Chrysanthemum extract could significantly inhibit hydrogen peroxide (H2O2)-mediated cell death in L-O2 hepatocytes. Propidium iodide staining and annexin V-PI dual staining revealed that the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Oxidative damage model using H 2 O 2 -induced L02 cells damage model. 33 In the following experiments, the cells were allowed to adhere for 12 h and the cell medium was replaced with 20 μM of the test compound for another 20 h, and then the cells were exposed to H 2 O 2 (1 mM) for 4 h.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative damage model using H 2 O 2 -induced L02 cells damage model. 33 In the following experiments, the cells were allowed to adhere for 12 h and the cell medium was replaced with 20 μM of the test compound for another 20 h, and then the cells were exposed to H 2 O 2 (1 mM) for 4 h.…”
Section: Methodsmentioning
confidence: 99%
“…Han et al have shown that the hydroxytyrosol treatment could increase the activities of SOD and GSH-Px, and decrease the MDA level in mice serum through down-regulating the glycerophospholipid metabolism pathway [29]. Meanwhile, a previous study showed that the chrysanthemum extract could increase SOD and GSH-Px activities in LO2 hepatocytes by down-regulating the purine metabolism pathway [30].…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…Various bioactive components in Chrysanthemum VO can improve the antioxidant defense ability of the body by inhibiting lipid peroxidation or regulating antioxidant enzyme levels by participating in other related antioxidant stress signaling pathways [43] , such as the activation of nuclear factor erythroid 2-related factor 2 (Nrf2)-related antioxidant pathways [49] . According to a recent study, germacrane-type sesquiterpenoids in Chrysanthemum can promote the dissociation and translocation of Nrf2 from Kelch-like ECH-associated protein 1 (Keap1) to the nucleus by anchoring to the Kelch domain-binding site of Keap1, thereby reducing the accumulation of reactive oxygen species (ROS) and increasing glutathione and heme oxygenase-1 levels and superoxide dismutase activity, thereby protecting the liver against oxidative damage [50] .…”
Section: Involvement In Other Antioxidant Pathwaysmentioning
confidence: 99%